The Osmotic Self and Language Arts Pedagogy - Kristie S. Fleckenstein (Journal of the Assembly for Expanded Perspectives on Learning, 1997)
Educators should evolve a pedagogy that privileges a participatory self, in which ego boundaries are permeable.